Augmented reality to INSTIKI building recognition using marker based method - Putu Wirayudi Aditama; Ketut Laksmi Maswari; I Kadek Agus Aristia Permana (Jurnal Mantik, 2023)
The fourth industrial revolution has been initiated by advances in augmented and virtual technologies. AR technology can simulate the actual world in a virtual setting, allowing for more effective trials. In the context of educational institutions such as the Indonesian Institute of Business and Technology (INSTIKI), there are still many locations where information is disseminated through media such as brochures. The objective of this study is to use Augmented Reality (AR) to introduce facilities in the INSTIKI campus building via a marker-based method. The contribution of this study is the application of augmented reality (AR) technology to improve the community's access to information about campus building facilities and specifications. The results of this study are augmented reality (AR) applications for the introduction of INSTIKI campus buildings that have undergone compatibility testing, distance testing, and user response testing with a total average score of 88.9%, which is a very good rating. In order for this augmented reality (AR) application to function as a digital media to promote the INSTIKI campus, the average value of 88.9% must be derived from the percentage of respondents who rated the application as either very good or decent.